Roma Toah: Social Construction of Inheritance Division of The Bangkalan Madura Community - Mohammad Hipni (IAIN Manado, 2023)
Applying Islamic law within the framework of social culture is never complete for research. Certain social entities understand Islamic law, originating from revelation to produce unique legal products. Roma Toah inheritance in Madurese society is a division of inheritance intended for all heirs without being based on the individual principle as in Islamic inheritance law in general. This study aims to understand the construction of social, cultural, and religious inheritance of Roma Toah in the people of West Madura, who are known to be firm in upholding their religious teachings. This study uses a qualitative method approach using a socio-legal approach. This study uses social construction analysis so that the meaning of the inheritance of Roma Toah can be well understood. This research resulted in the following findings; first, the legacy of Roma Toah survives based on the local wisdom of the Madurese community, based on two aspects that align with Islamic values; maintaining family ties intact and family economic resilience. Second, by using social construction analysis based on three phases; externalization, objectification, and internalization, the Roma Toah inheritance is built on a harmonious blend of culture, social, and religion through the legitimacy of traditionalist Madurese Ulama so that it is considered a system that does not conflict with Islamic values in maintaining family and economic integrity.